2009
DOI: 10.1111/j.1524-4725.2009.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Optical Coherence Tomography Imaging in the Diagnosis of Non-Melanoma Skin Cancer and Benign Lesions Versus Normal Skin

Abstract: OCT features in NMSC are identified, but AK and BCC cannot be differentiated. OCT diagnosis is less accurate than clinical diagnosis, but high accuracy in distinguishing lesions from normal skin, crucial for delineating tumor borders, was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
194
3
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 187 publications
(207 citation statements)
references
References 37 publications
7
194
3
3
Order By: Relevance
“…[17][18][19][20][21][22][23][24][25] The ability of OCT to differentiate NMSC lesions from normal skin has also been assessed in the clinical setting using observer-blinded evaluation by dermatologists and pathologists. 26 To date, however, most of the clinical investigations in skin disease using OCT have used two-dimensional (2-D) images or relatively low resolution. Initial reports using OCT for skin imaging revealed significantly improved resolution over high-frequency ultrasound imaging, as well as better imaging depth and field of view than with RCSM or TPFM.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25] The ability of OCT to differentiate NMSC lesions from normal skin has also been assessed in the clinical setting using observer-blinded evaluation by dermatologists and pathologists. 26 To date, however, most of the clinical investigations in skin disease using OCT have used two-dimensional (2-D) images or relatively low resolution. Initial reports using OCT for skin imaging revealed significantly improved resolution over high-frequency ultrasound imaging, as well as better imaging depth and field of view than with RCSM or TPFM.…”
Section: Introductionmentioning
confidence: 99%
“…Distinguishing normal skin and basal cell carcinoma may be possible using PS-OCT, as a pilot study by Strasswimmer et al concluded [218]. However, in a recent study by Mogensen et al conducted on more than 100 patients with different types of lesions, PS-OCT could not improve the diagnostic acurracy compare to the assessment based on structural OCT images [219].…”
Section: Dermatologymentioning
confidence: 90%
“…The difference between OCT and reflectance confocal microscopy is the ability of OCT to image to a depth of 1 mm; however, this increased penetration depth comes at the cost of reduced resolution. Ultimately, of course, this method also aims at reducing the need for invasive biopsies by providing reliable images that allow for diagnostic decisions and for treatment response monitoring [16][17][18].…”
Section: Fortschritte In Der Dermatologiementioning
confidence: 99%